LAW AND THE REGULATION OF SCIENTIFIC RESEARCH trusting experts. - Davies, Mark. ([S.l.] : ROUTLEDGE, 2022)
Scientific research is fundamental to addressing issues of great importance to the development of human knowledge. Scientific research fuels advances in medicine, technology and other areas important to society and has to be credible, trustworthy and able to command confidence in the face of inevitable uncertainties. Scientific researchers must be trusted and respected when they engage with knowledge acquisition and dissemination and as ethical guardians in their education and training roles of future generations of researchers. The core values of scientific research transcend disciplinary and national boundaries and approaches to the organisation and oversight of research systems can impact significantly upon the ethics and conduct of researchers. This book draws upon legal expertise to critically analyse issues of regulation, conduct and ethics at the important interface between scientific research and regulatory and legal environments. In so doing it aims to contribute important additional perspectives to the existing literature. Case studies are engaged with to assist with the critical analysis of the current position and the consideration of future possibilities. The research for this book was up to date as of 1 January 2022. The book will be of interest to academics in the fields of science, law and policy; science and law students; and scientific researchers at more advanced stages of their careers. Research professionals in government and the private sector and legal practitioners with interests in the regulation of research should also find the work of interest.
OCLC-licensed vendor bibliographic record.
Keywords: Research -- Law and legislation; LAW / Science & Technology; LAW / Administrative Law & Regulatory Practice; LAW / Ethics & Professional Responsibility